Phosphoenolpyruvate-dependent phosphotransferase system enzyme III and plasmid-encoded sucrose transport in Escherichia coli K-12. - Lengeler, J W (1982)
The phosphoenolpyruvate-dependent carbohydrate:phosphotransferase system enzyme IISCR, specific for and regulated by sucrose, was analyzed in derivatives of Escherichia coli K-12 carrying the sucrose plasmid pUR404. Enzyme IIScr, coded for by gene scrA of the plasmid, depended for its transport and phosphorylation activity directly on the phosphotransferase system enzyme IIIGlc, Scr, coded for by the chromosomal gene crr.